An assessment of growth ring identification in subtropical forests from northwestern Argentina - Ferrero, Maria Eugenia (2014)
Most subtropical forests in South America are located in regions with a marked seasonality in precipitation, which may induce the formation of annual bands in woody species. Due to the lack of precise information on tree-ring visibility, we evaluated the wood characteristics of 37 tree species in the subtropicalYungas and Chaco forests from northwestern (NW) Argentina. Anatomical features associated with the delimitation of growth bands were examined to establish the presence of tree rings. Different forest types reflect the precipitation gradients and wood anatomical features vary accordingly. Characteristics of wood structure are closely related to the dominant climatic patterns of each forest, revealing a common pattern of anatomical arrangements in terms of water transport and safety. In the Chaco and transitional forests, ring boundaries are related to marginal parenchyma whereas in montane forests growth ring boundary is mostly associated with the presence of thicker fibers at the end of the ring. The largest proportion of species with clearly marked growth rings occurs in the montane forest type of NW Argentina. Clear growth rings is a requisite for dendrochronological applications, hence the present work represents the first regional attempt to address the potential of subtropical species in South America to be used in dendrochronological studies.